Formative research for an mHealth program to improve the HIV care continuum in South Africa. Issue 6 (2nd June 2020) - DiAndreth, Lisa; Krishnan, Nandita; Elf, Jessica L.; Cox, Sarah; Tilchin, Carla; Nthulana, Munei; Jarrett, Brooke; Kronis, Nadya; Dupuis, Elisa; Motlhaoleng, Katlego; Chon, Sandy; Martinson, Neil; et al.
ABSTRACT: In South Africa, high attrition rates throughout the care continuum present major barriers to controlling the HIV epidemic. Mobile health (mHealth) interventions may provide innovative opportunities for efficient healthcare delivery and improving retention in care. In this formative research, we interviewed 11 patients and 28 healthcare providers in North West Province, South Africa, to identify perceived benefits, concerns and suggestions for a future mHealth program to deliver HIV Viral Load and CD4 Count test results directly to patients via mobile phone. Thematic analysis found that reduced workload for providers, reduced wait times for patients, potential expanded uses and patient empowerment were the main perceived benefits of an mHealth program. Perceived concerns included privacy, disseminating distressing results through text messages and patients' inability to interpret results. Participants felt that an mHealth program should complement face-to-face interactions and educational information to interpret results is needed. Providers identified logistical considerations and suggested protocols be developed. An mHealth program to deliver HIV test results directly to patients could mitigate multiple barriers to care but needs to be tested for efficacy. Concerns identified by patients and providers must be addressed in designing the program to successfully integrate with health facility workflow and ensure its sustainability.